2020
DOI: 10.1016/j.radonc.2020.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Impact of non-adherence to radiotherapy on 1-year survival in cancer patients in Catalonia, Spain

Abstract: Background: This study aims to assess the effects of non-adherence to external beam radiation therapy in cancer patients receiving treatment with a curative. Methods: This retrospective cohort study collected health records data for all cancer patients treated with external beam radiotherapy with curative intent in 2016 in Catalonia, Spain. Adherence was defined as having received at least 90% of the total dose prescribed. A logistic regression model was used to assess factors related to non-adherence, and its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 20 publications
0
7
1
Order By: Relevance
“…Despite the large number of patients being offered RT, the noncompliance rate in our department is 2.28%, significantly less than the reported incidence in other institutes, though the definitions of noncompliance vary across studies. 1 4 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 The distribution of gender (males 112; 56.9%) was reflective of the routine registrations in the year 2019 emphasizing that there is no gender-specific predilection for noncompliance in our study. The same was true for the marital status and age of the patients.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Despite the large number of patients being offered RT, the noncompliance rate in our department is 2.28%, significantly less than the reported incidence in other institutes, though the definitions of noncompliance vary across studies. 1 4 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 The distribution of gender (males 112; 56.9%) was reflective of the routine registrations in the year 2019 emphasizing that there is no gender-specific predilection for noncompliance in our study. The same was true for the marital status and age of the patients.…”
Section: Discussionmentioning
confidence: 50%
“…6 7 8 9 10 11 The studies published globally too mention a wide range of noncompliance across institutions and regions ( Table 5 ). 1 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 The comparison of these results from these studies is challenging as the definition of noncompliance varies. The studies from our country show variable but high noncompliance rate across a spectrum of urban tertiary care centers, academic ones, and centers operating in rural part of the country.…”
Section: Discussionmentioning
confidence: 99%
“…Our results contrast with findings reported for higher‐income countries, such as the United States and Spain, where radiotherapy completion rate among breast cancer patients were 97% and 99.3%, respectively. 9 , 11 This difference may be explained by the availability of abundant radiotherapy resources and the stricter medical supervision involved in the management of breast cancer treatment in developed countries. 9 , 11 For 261 million Indonesian people in 2017, 261 radiotherapy machines were needed to achieve a 1 MV machine per million population.…”
Section: Discussionmentioning
confidence: 99%
“… 8 Few researchers have addressed OTT and radiotherapy completion rates among breast cancer patients. 9 , 10 , 11 , 12 , 13 , 14 In this study, we explore problems that breast cancer patients experience with radiotherapy, focusing on OTT and radiotherapy completion rates. We hypothesize that the average OTT of breast cancer patients in Indonesia is longer than standard, and the radiotherapy completion rate is suboptimal.…”
Section: Introductionmentioning
confidence: 99%
“…Reports on the incidence of treatment interruptions vary on the basis of the primary site and the treatment setting, but reports range from 20% to 71% while the incidence of treatment discontinuation range from 13% to 61%. 36,[38][39][40][41][42][43][44][45] Compliance with a planned radiotherapy course is crucial as multiple studies have shown that treatment delays and interruptions are associated with worse oncologic outcomes. 34,35 The impacts of treatment interruption or discontinuation also have knock on effects on available resources.…”
Section: Hypofractionation and Treatment Compliancementioning
confidence: 99%